2. Work in Progress: PhD thesis. Religious connectivity in Boeotia. The sanctuaries of the Kopais region (abstract) - Solazzo, Alice (Teiresias Journal Online, 2025)
Alice SOLAZZO (Università degli Studi di Palermo, Universität Münster) PhD thesis: Religious connectivity in Boeotia. The sanctuaries of the Kopais region (abstract)